2010
DOI: 10.1192/pb.bp.109.025908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of catatonic signs in acute psychiatric patients in Scotland

Abstract: Aims and methodConcerns have been raised that catatonia is underdiagnosed. Prevalence varies (1.3-32%) depending on diagnostic criteria. We used the Modified Rogers Scale to rate catatonic signs in patients consecutively admitted to three psychiatric wards over a 10-month period.ResultsThe prevalence of patients demonstrating any catatonic signs was at least 7.9-19.1%. The most common catatonic signs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“… 14 , 15 Concerns have been raised that catatonia is underdiagnosed. One study 16 found that in Scotland the prevalence of catatonia varied depending on the diagnostic criteria used, ranging from 1.3 to 32%. In that study the prevalence of psychiatric patients demonstrating any catatonic signs was at least 7.9–19.1%.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Concerns have been raised that catatonia is underdiagnosed. One study 16 found that in Scotland the prevalence of catatonia varied depending on the diagnostic criteria used, ranging from 1.3 to 32%. In that study the prevalence of psychiatric patients demonstrating any catatonic signs was at least 7.9–19.1%.…”
Section: Discussionmentioning
confidence: 99%
“…It should be borne in mind; however, that catatonia and dementia are not mutually exclusive diagnoses and neurologic conditions associated with catatonia are protean including herpetic encephalitis, frontal lobe trauma, paraneoplastic, epilepsy, syphilis and temporal lobe infarction [7]. Prevalence of catatonia in dementia was circa 15% in a study from Scotland [8]. Cardinal catatonic features commonly overlap with advanced dementia [9].…”
mentioning
confidence: 99%
“…Für solche Symptome speziell entwickelte Instrumente, wie beispielsweise die Northoff Catatonia Scale [22] oder die Katatonie-Rating-Skala [16], kommen sowohl im klinischen Alltag als auch in Forschungsprojekten eher selten zum Einsatz. Systematische Untersuchungen zeigen jedoch, dass die Prävalenz katatoner Symptome mit bis zu 19 % bei Patienten mit akuten psychischen Störungen wahrscheinlich höher als üblicherweise angenommen ist [23]. Die Schwierigkeiten der differenzierten Erfassung psychomotorischer Symptome mögen auch dazu beigetragen haben, dass das Interesse am katatonen Subtyp der Schizophrenie stark abgenommen hat und gar dessen Existenz infrage gestellt wird [19].…”
unclassified